The ultimate guide to electronic marketing for small business : - Antion, Tom (John Wiley & Sons, Inc., 2005)
The Ultimate Guide to Electronic Marketing for Small Business gives the small business owner or aspiring entrepreneur the real-world tools and tactics to market their small business around the world with little investment and even less risk. Full of practical ideas on reaching new customers and increasing sales, this book will make a real difference in the success rate of small businesses and start-ups everywhere